PENGARUH CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Uun Sunarsih; Ade Refany Oktavia (Jurnal Reviu Akuntansi dan Keuangan, 2017)
This study aims to examine the effect of corporate governance on tax avoidance. This research isconducted on mining companies listed in BEI period 2012-2015. The method used purposivesampling and obtained 10 companies. The data used is secondary data can be downloadedwww.idx.co.id. The results of this study conclude ROA does not affect tax avoidance, because thecompany tries to obtain high profit as an indicator of company performance. Institutional ownership has no effect, it may not be able to supervise any management decision. Managerialownership is influential, it is possible that managerial ownership can increase optimal supervision. The board of independent commissioners is influential, indicating the greater the composition of the commissioner the better the performance. Audit committee is influential, indicatingthe number of audit committees able to improve supervision on management. Audit qualityinfluences indicates that the audit services used can reduce tax avoidance measures.Keywords: Return On Asset, Corporate Governance Mechanism, Tax Avoidance